Over Two Decades of African Commission on Human and Peoplesa Rights: Flying or Fledgeling (Global Journal of Human-Social Science, 2012)
This article examines the operation and performance of African Commission on Human and Peoples Rights since 2007 when it was constituted It takes a survey of the historical background of the Commission and considers its establishment membership and independence in comparative perspective with the Inter- American Commission on Human Rights and former European Commission on Human Rights It points out that taking into consideration the large size of Africa it is crucially important that the composition of the Commissioners be enlarged The article evaluates the functions failures and achievements of the Commission and evaluates the impediments that hinder the Commission from effective performance of its functions since inception It argues that while some of the obstacles can be overcome by the amendment of the Charter or adoption of Protocols to the Charter others require political will by African leaders The article also answers the question whether with the establishment of the African Court of Human and Peoples Rights and African Court of Justice and Human Rights that might replace it the African Commission should be abolished or the Commission should be strengthened by overcoming the obstacles that hinder it from effective performance of its mandates
Keywords: African Commission; Flying or Fledgeling